Penerapan Model Pembelajaran Kooperatif Menggunakan Media Kartu untuk Meningkatkan Keaktifan Belajar pada Mata Pelajaran Bahasa Arab - Risya Arrumaisya; A. Sulaeman (UM Purwokerto Press, 2023)
Teaching and learning activities cannot be separated from the use of learning media. Learning media has become a requirement for the activity to take place. Motivation to learn in learning is indispensable. It aims to create an active classroom atmosphere or produce perfect scores because of students' interest in learning materials. One of the obligations of teachers in the learning process is to have methods in the effectiveness and efficiency of learning time. Teachers must choose and develop the right learning methods so that students are enthusiastic and do not feel bored. The purpose of this study is to determine the concept, process, and results of the application of the cooperative learning model with card media in Arabic class VIII subjects at Muhammadiyah Sokaraja Junior High School. This research is a type of qualitative research with data collection techniques through observation and interviews. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions. The application of the cooperative learning model using card media in Arabic subjects began to be carried out with preliminary activities, core activities, and closing activities. The results of the application of this cooperative learning model show that learners divide tasks with each other, such as translating words, writing answers, and concluding answers. Learners can follow and be more active in learning, learners are also easy to understand the materials that have been explained by the teacher.